Are the Menstrual Characteristics Similar in Adolescent and Adult Women with Cerebral Palsy? - Dogan, Hanife; Turker, Duygu; Coban, Ozge; Basol Goksuluk, Merve; Ozengin, Nuriye; Un Yildirim, Necmiye (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: This study aimed to compare the menstrual-health characteristics of adult and adolescent women with cerebral palsy. STUDY DESIGN: This cross-sectional study included 74 women who were diagnosed with cerebral palsy. Among 74 women with cerebral palsy, women between the ages of 10-18 formed the adolescent cerebral palsy group (n= 36), and women between the ages of 19-30 formed the adult cerebral palsy group (n=38). Gross motor function levels of women with cerebral palsy were determined by gross motor function classification system expanded and revised. Menstrual-health characteristics were evaluated with a self-report questionnaire. RESULTS: The median age in the adult cerebral palsy group (23.5 (19-29) years)) was higher than the adolescent cerebral palsy group (16.5 (11-18) years)) (p<0.001). The median age of menarche in the adult cerebral palsy group (14 (7-18) years) was higher than in the adolescent cerebral palsy group (13 (9-17) years)) (p=0.017). The presence of dysmenorrhea in the adolescent cerebral palsy group (35 women with dysmenorrhea) was more common than in the adult group (30 women with dysmenorrhea (p=0.016). The menstrual suppression treatment, length of menstruation, pain onset time, pain duration, pain medicine usage during menstruation, the highest intensity of pain experienced during the menstrual period, number of drugs, use of pain relief methods, number of days absent from school or work, type and the number of menstruation products, presence and the reason of discomfort scores of questions and gross motor function classification system expanded and revised levels were similar in both groups (p>0.05). CONCLUSION: Dysmenorrhea was more prevalent in adolescent women with cerebral palsy than in adults with cerebral palsy. Providing training that raises awareness and behavior-changing education for women with cerebral palsy and their caregivers can help to improve gynecological health.